The Role of Coccinella undecimpunctata L. in Suppressing the Population Level of Schizaphis graminum (Rond) and Increase the Yield in Wheat Plantation at Dakahlia Governorate, Egypt. - Ghanim, A. A.; El-Adl, M. A. (Contributions to Entomology = Beiträge zur Entomologie, 1991)
Field studies under special metal cages were carried out in wheat fields fo the two successive years 1985 and 1986 to evaluate the efficiency of Coccinella undecimpunctata L. in controlling Schizaphis graminum (Rond) and ist indirect effect on wheat yield. The study was excuted in the wheat fields of the Experimental Research Station, Faculty of Agriculture, Mansoura University. The obtained results showed the efficacy of C. undecimpunctata in regulating the population level of S. graminum (Rond) with a degree depends on the existance ratio between the pupulations of the two species. The injury in the wheat crop caused by S. graminum (Rond) compared with the control reached 28,06% in 1985 and 23,53% in 1986, while the aphid increasing rates were 32,92 times in 1985 and 26,94 times in 1986 comparing with the aphid numbers found at the beginning of the artificial infestation. The presence of one predator larva: 80-100 aphid individuals resulted in an economic injury in wheat crop that reached 18,88% in 1985 and 17.04% in 1986. At this ratio 32,80%, and 31,75% reductions in the aphid numbers were recorded in 1985 and 1986 respectively. While the presence of one predator adult: 40-50 aphids or one predator first instar larva: 20-25 aphid individuals induced no economic damage in the crop, as the crop loss weas 3,06% in 1985 and 2,14% in 1986 with the first ratio (one predator adult: 40-50 aphids) and 4,08% in 1985 and 3,21% in 1986 with the second ratio (one predaor larva: 20-25 aphids). The first ratio caused reduction in the aphid index reached 89,71% in 1985 and 91,38% in 1986, while the second ratio induced 88,19% in 1985 and 89,77% in 1986.